Design and evaluation of a novel expandable gastroretentive film for sustained Metoprolol release - Mustafa Musa Khalaf; Oday Sajad; Rana M. F. Sammour; Bazigha K. Abdul Rasool (PLoS ONE, 2026)
Gastroretentive drug delivery systems (GRDDS) are designed to prolong gastric residence time and improve drug bioavailability. Among these, swelling-based expandable films offer the dual advantage of increased gastric retention and controlled drug release. Metoprolol tartrate, a β1-receptor blocker with a short half-life and low oral bioavailability, was selected as the model drug. This study aimed to develop and evaluate a novel swelling-based expandable gastroretentive film of Metoprolol using a 4 × 4 full factorial design to systematically investigate the effects of HPMC and Carbopol 934 concentrations. Sixteen formulations (F1–F16) were prepared by solvent casting and swelling index (SI) and in vitro drug release were chosen as response variables. The optimized film (F14) exhibited a high SI and sustained drug release, delivering ≈86% of Metoprolol over 12 hours. Kinetic modeling demonstrated first-order and Higuchi release patterns with a non-Fickian mechanism, while model-independent parameters (AIC, MSC, similarity factors) supported these findings. Characterization studies confirmed the robustness of F14: FTIR and XRD revealed no drug–polymer interaction and an amorphous drug state, while SEM showed a uniform surface with interconnected pores. Mechanical testing confirmed desirable tensile strength and flexibility. Radiographic evaluation in rabbits demonstrated that F14 expanded and remained in the stomach for up to 12 hours, validating its gastroretentive capacity. Furthermore, short-term stability testing under accelerated ICH conditions confirmed the film’s physical and chemical stability and sustained-release performance for 6 weeks. In conclusion, the optimized expandable film (F14) combined swelling, gastric retention, and sustained drug release, highlighting its promise as a gastroretentive platform to enhance Metoprolol bioavailability and efficacy.